Georgette Heyer, History and Historical Fiction - Rayner, Samantha J.; Wilkins, Kim (UCL Press, 2021)
The Nonesuch is the name of one of Georgette Heyer's most famous novels. It means a person or thing without equal, and Georgette Heyer is certainly that. Her historical works inspire a fiercely loyal, international readership and are championed by literary figures such as A. S. Byatt and Stephen Fry. Georgette Heyer, History, and Historical Fiction brings together an eclectic range of chapters from scholars all over the world to explore the contexts of Heyer's career. Divided into four parts - gender; genre; sources; and circulation and reception - the volume draws on scholarship on Heyer and her contemporaries to show how her work sits in a chain of influence, and why it remains pertinent to current conversations on books and publishing in the twenty-first century. Heyer's impact on science fiction is accounted for, as are the milieu she was writing in, the many subsequent works that owe Heyer's writing a debt, and new methods for analysing these enduring books. From the gothic to data science, there is something for everyone in this volume; a celebration of Heyer's 'nonesuch' status amongst historical novelists, proving that she and her contemporary women writers deserve to be read (and studied) as more than just guilty pleasures.